PENGARUH CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN, HAK ARUS KAS, DAN DISCLOSURE OF RPT TERHADAP TRANSAKSI PIHAK BERELASI - Rikhan Agustinah; Mr. Sumarno; Abdulloh Mubarok (Multiplier: Jurnal Magister Manajemen, 2018)
The purpose of this research is 1) to obtain empirical evidence of Corporate Governance influence on Related Party Transaction, 2) to obtain empirical evidence of the influence of Ownership Structure on Related Party Transaction, 3) to obtain empirical evidence of the influence of Cash Flow Right to Related Party Transaction, 4) to obtain empirical evidence of Disclosure of rpt influence on the Related Party Transaction, 5) to obtain empirical evidence of Corporate Governance, Ownership Structure, Cash Flow Right, Disclosure of rpt to Related Party Transaction. The result of the research is that there is no influence of corporate governance to related party transaction, there is positive influence of ownership structure to related party transaction, there is positive influence of cash flow right to related party transaction, there is positive influence of disclosure of rpt to related party transaction, there is influence of Corporate Governance, Ownership Structure, Cash Flow Right, Disclosure of rpt to Related Party Transaction. The value of determination coefficient obtained is 0.314. it can be concluded that the contribution of corporate governance variable. Ownership structure, cash flow right, and disclosure of rpt to related party transaction amounted to 31.4% while 68.6% was caused by other unexplained factors. Keywords : Corporate Governance, Ownership Structure, Cash Flow Right, Disclosure of rpt, Related Party Transaction.